2001
DOI: 10.1006/bijl.2000.0485
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow and effective population size in Lepanthes (Orchidaceae): a case for genetic drift

Abstract: Genetic drift can play an important role in population differentiation, particularly when effective population sizes are small and gene flow is limited. Such conditions are suspected to be common in the species-rich Orchidaceae. We investigated the likelihood of genetic drift in natural populations of three endemic species of Lepanthes (Orchidaceae) from Puerto Rico. We estimated effective population size, Ne, using three ecologically based methods. Two of the three estimates were based on variance in reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 12 publications
3
70
0
4
Order By: Relevance
“…Studies based on allozymes found high genetic differentiation among populations of Goodyera procera (G ST ϭ 0.52, Wong and Sun 1999), Lepanthes rubripetala (F ST ϭ 0.293, Tremblay and Ackerman 2001) and Pterostylis gibbosa (G ST ϭ 0.15, Sharma et al 2000). These results were interpreted as the consequence of habitat fragmentation, inbreeding, founder effects, and genetic drift.…”
Section: Fig 4 Genotype Assignment Tests Based On Cavalli-sforza's mentioning
confidence: 98%
See 1 more Smart Citation
“…Studies based on allozymes found high genetic differentiation among populations of Goodyera procera (G ST ϭ 0.52, Wong and Sun 1999), Lepanthes rubripetala (F ST ϭ 0.293, Tremblay and Ackerman 2001) and Pterostylis gibbosa (G ST ϭ 0.15, Sharma et al 2000). These results were interpreted as the consequence of habitat fragmentation, inbreeding, founder effects, and genetic drift.…”
Section: Fig 4 Genotype Assignment Tests Based On Cavalli-sforza's mentioning
confidence: 98%
“…In Ophrys populations, typically only a small fraction of individuals set seed each year (Neiland and Wilcock 1998). As a consequence, genetic drift could play an important role in the evolution and diversification of Ophrys and other deceit-pollinated orchids (Kiester et al 1984;Tremblay and Ackerman 2001). So far, however, little is known about the levels and patterns of genetic variation in sexually deceptive orchid species.…”
mentioning
confidence: 99%
“…15 Molecular studies may prove useful in improving spatial genetic variation knowledge and for delineating evolutionary genetic processes. [16][17][18][19] Neutral markers such as amplified fragment length polymorphisms (AFLP 20 ) or simple sequence repeats (SSR 21,22 ) are commonly used to screen collections. In previous studies, the diversity and the structure in the genus Campanula was studied using nuclear (ISSR) and chloroplast (cpSSR) markers in C. pollinensis Podlech and C. pseudostenodon Lac.…”
Section: Introductionmentioning
confidence: 99%
“…Tremblay & Ackerman (2001), trabalhando com orquídeas epifíticas do gênero Lepanthes na Costa Rica, situaram tamanho populacional e distribuição espacial dos indivíduos como parâmetros fundamentais na seleção natural, atuando por outro lado, a deriva genética na diferenciação populacional. Da mesma forma, o estudo de populações em diferentes estádios ontogenéticos fornece informações pertinentes ao longo do ciclo de vida da espécie (Santos 2002).…”
Section: Introductionunclassified
“…Segundo Zimmermam & Aide (1989), o sucesso reprodutivo está correlacionado com o tempo de vida de cada indivíduo, sendo que este é quase totalmente desconhecido no caso de orquídeas (Tremblay & Ackerman 2001). Esta relação entre números de indivíduos jovens e adultos é fundamental à compreensão dos padrões populacionais de cada espécie (Wells & Cox 1991).…”
Section: Introductionunclassified